Impact of natural disasters on the western Hubei power grid and its anti‐disaster enhancement measures. Issue 16 (17th December 2018) - Cai, Defu; Li, Xiaoping; Shi, Tongqin; Wang, Ying; Zhou, Kunpeng; Lu, Shengwei; Cao, Kan; Wang, Wenna
Abstract : The western mountain area of Hubei Province has obvious vertical climate and micro‐climate features. It is a place where natural disasters occur frequently. The natural disasters have recently caused several large‐scale and long‐time power blackouts in the western mountain area of Hubei Province. This study analyses the damage to the power grid with voltage level from 220 to 10 kV in western Hubei Province caused by natural disasters from 2008 to 2016. The influence features of natural disasters on the western Hubei power grid are researched from four aspects, including natural disaster type, grid voltage level, occurrence time of natural disaster and line outage frequency. The causes of damage to the western Hubei power grid are studied from five aspects, including grid structure, design, equipment, construction, operation and maintenance. Also, the anti‐disaster enhancement measures of the western Hubei power grid are proposed from the aspects of grid planning, design, equipment transformation, construction, operation and maintenance. The research results can provide a reference for other regional power grids to carry out research on resisting natural disasters and provide a guidance to improve anti‐disaster ability of the power grid.